(untitled) (Ozone Therapy Global Journal, 2019)
Introduction: Infection of the cervix by HPV is one of the most frequent sexually transmitted diseases in women in reproductive age today, with ozone therapy being an alternative treatment in which patients are increasing their interest. Objective: To analyze the cytological changes in the cervix of patients who presents HPV injuries after the application of Ozonotherapy in a lapse of one month and a half according to the Madrid declaration of Ozonotherapy. Materials and Methods: A clinical, epidemiological, prospective and uncontrolled study of Ozone intervention in female patients between 18 and 36 years and diagnosis of HPV who attended the public and private gynecological consultation in the State of Aragua, between July and November 2017. Results: 25 patients who met the inclusion and exclusion criteria were treated. During the evolution of the patients, a first group (n = 12) had a rapid improvement in 57.1% (at 3 weeks) while the answer in the remaining group (n = 9) was later 47.9% (at 6 weeks) ((P <0.01) (X2 corrected from 13.66)) No differences according to age group. There were no adverse effects during the treatment (95% CI: 83.89% 100.00%). Conclusion: It is concluded that there is a positive correlation between the ozone therapy treatment and the remission of the infectious process and the structural changes of the cervix